SUBSTANTIVE AND METHODOLOGICAL ASPECTS STUDY OF THE DISCIPLINE «EXPRESSIVE READING» STUDENTS OF PEDAGOGICAL SPECIALTIES - Kachak, Tetiana; Krul, Larisa (Mountain School of Ukrainian Carpaty, 2020)
In the process of formation of literary competence and pedagogical skills of the educator, the teacher is extremely important person to develop professional qualities, communication skills, and expressive reading. The search for effective ways to achieve this goal in modern educational conditions of distance or blended learning is an urgent problem that needs to be considered both at the level of scientific and theoretical, and at the level of analysis of practical experience. The article analyzes the content and methodological aspects of studying the discipline "Expressive reading" by students of pedagogical specialties, taking into account challenges and needs of our time; the relevance of the course is argued; the priorities of personal pedagogical experience are outlined. The tools of the system-activity approach, typological comparison provided the analysis of thematic blocks of the discipline and argumentation of its role in the professional training of the teacher. Empirical research methods (pedagogical observation of the process, testing of new forms and methods, questionnaires), systematization and generalization of the results of practical experience were used to determine the methods of teaching this course in the conditions of classroom and distance learning. Expressive reading is not only the art of meaningful, correct, emotional reading in order to convey information and influence the listener, but also a tool for teacher-student interaction. That is why in the professional training of educators and primary school teachers an important role is given to the disciplines of literary and methodological direction. The content of the course "Expressive reading" meets the demands of modern educational discourse and aims to expand knowledge of the theory of the art of speech and improve the performance skills of future educators and teachers; acquaintance with methods and techniques of teaching children expressive reading. The methodology of teaching this course in classroom and distance learning is not different in content, but in the chosen methods and forms of work, the level of involvement of digital tools and information and computer technology. During the classroom training, a lecture-visualization, a binary lecture, a lecture-conference, group work in practical classes, presentations of individual projects were held. In the conditions of distance learning they practiced binary and integrated online lectures, online meeting with the speaker or actors, online master class, webinar, online readers' competition. Author's methods and forms of work are interesting and productive: literary five minute, creative interactive reading, and competitions of expressive reading videos, preparation and compilation of own portfolio, participation in literary projects.